2004
DOI: 10.1128/mcb.24.10.4384-4394.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Activation of Phosphatidylinositol 3-Kinase, βPix, Rac1, and Nox1 in Growth Factor-Induced Production of H2O2

Abstract: The generation of reactive oxygen species (ROS) in cells stimulated with growth factors requires the activation of phosphatidylinositol 3-kinase (PI3K) and the Rac protein. We report here that the COOHterminal region of Nox1, a protein related to gp91 phox (Nox2) of phagocytic cells, is constitutively associated with ␤Pix, a guanine nucleotide exchange factor for Rac. Both growth factor-induced ROS production and Rac1 activation were completely blocked in cells depleted of ␤Pix by RNA interference. Rac1 was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
166
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(178 citation statements)
references
References 46 publications
10
166
2
Order By: Relevance
“…It has been shown that growth factor-induced ROS generation is a result of sequential activation of EGFR, PI3K, bPix, Rac and NOX1 (Bae et al, 1997;Park et al, 2004). Here, we found remarkable increase in serum-independent, TCTPinduced ROS generation from NADPH oxidase, without cell death (Figures 4a and b).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It has been shown that growth factor-induced ROS generation is a result of sequential activation of EGFR, PI3K, bPix, Rac and NOX1 (Bae et al, 1997;Park et al, 2004). Here, we found remarkable increase in serum-independent, TCTPinduced ROS generation from NADPH oxidase, without cell death (Figures 4a and b).…”
Section: Discussionsupporting
confidence: 58%
“…As ROS generation by growth factor is related to sequential activation of EGFR and PI3K (Park et al, 2004), and Src has an important role in TCTP-induced EGFR transactivation (as demonstrated in this study), we examined whether TCTP-induced ROS generation depends on Src or PI3K, using Src-and PI3K-specific inhibitors, namely, PP2 and LY294002, respectively. Both PP2 and LY294002 completely blocked TCTPinduced ROS generation in MCF10A.…”
Section: Tctp-induced Src Activation J Jung Et Almentioning
confidence: 95%
“…This reduced mRNA expression and protein level in Cbl cos cells may be essential for inhibition of tumorigenicity, such as cell proliferation and spreading, before apoptosis and may induce apoptosis as observed in other tumor cells. 28 DNA-PKc, a critical DNA repair protein, travels to the cytoplasm and interacts with caspases 29 to induce apoptosis. Co-immunoprecipitation studies (Figures 3e and f) with the ARHGEF6 antibody suggest that DNA-PKc physically interacts with ARGEF6 in Cbl cos -treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…ARHGEF6, a Gcoupled receptor activated by phosphatidylinositol 3-kinase, modulates the cellular ROS level through Rac1. It also modulates ROS production from nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity in a growth factor-dependent manner, 28 and downregulation of ARHGEF6 inhibits cell spreading and adhesion. 27 Reduction of expression in Cbl cos may act downstream of DNA repair signaling and help to signal cells to maintain excess ROS, to stop proliferation and further adhesion of cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance a-Pix acts as a scaffold to integrate signals that arise from GPCRs with the activation of Cdc42 to drive chemotaxis. 90 In a related example b-Pix tethers NADPH oxidase-1 to Rac1 for activation, 91 a pathway that regulates production of reactive oxygen species that is important to kill pathogenic bacteria.…”
Section: Gefs and Gapsmentioning
confidence: 99%